Early Warning, Early Action and Early Finance (AWARE) Platform: technical guide - Alahacoon, Niranga; Amarnath, Giriraj (International Water Management Institute, 2023)
The AWARE platform, a vital component of CGIAR's Climate Resilience initiative, stands as a crucial tool connecting early warning systems, proactive measures, and timely financial interventions. Designed for anticipatory action, AWARE empowers stakeholders to mitigate the impact of disasters before they occur, emphasizing multi-level coordination and collaboration for effective responsiveness. AWARE disseminates comprehensive information across climate, market dynamics, health, nutrition, and population displacement. It fosters collaborative efforts among diverse partners, promoting joint actions to strengthen preparedness and streamline response mechanisms. The platform targets government departments, agencies, humanitarian organizations, and funders to facilitate anticipatory action, identifying risks and formulating plans. Comprising six major modules, the report primarily focuses on Early Warning, Early Action, and Early Finance. The Early Warning module offers forecast and monitoring indicators, visualized through a step-by-step process. Early Action involves three phases: preparedness, readiness, and active, allowing users to input actions and collaborate seamlessly. Early Finance ensures financial resources are in place for interventions through a meticulous assessment. The report provides detailed guidance on utilizing the AWARE platform, featuring map preferences, Early Warning visualization, and Early Action protocols. It delves into forecasting indicators such as OpenWeather, NOAA Global Forecast Systems (NOAA-GFS), and International Research Institute for Climate and Society (IRI), and monitoring indicators like dry spell, Soil Moisture Condition Index (SMCI), and Integrated Drought Severity Index (IDSI). Flood indicators include Accumulated Rainfall (GPM), Flood (ESA), Flood (NASA), GLOFAS, and GeoGlows. Early Action, a key component, involves a step-by-step approach and accommodates user and administrator roles. Users can add, edit, and visualize early action protocols, fostering collaboration. Early Finance ensures financial backing for interventions, and the system generates comprehensive reports, facilitating information sharing. The training manual concludes by emphasizing the user-friendly nature of the guide, with interactive symbols, meaningful indicators, and a breakdown of modules. It encourages users to leverage map preferences for diverse base layers, enhancing data visualization.